Monthly blood transfusions decrease after four months of azacitidine. Issue 2 (20th April 2015) - Tseng, E.; Prica, A.; Zhang, L.; Mittmann, N.; Seung, S. J.; Callum, J.; Kim, T.; Wells, R. A.; Buckstein, R.
<x xml:space="preserve">Abstract</x> Background and Objectives Azacitidine (AZA) improves overall survival and transfusion independence in patients with myelodysplastic syndrome (MDS). We aimed to quantify the reduction in red blood cell (RBC) transfusions and to determine when this reduction occurs, in MDS patients treated with AZA. Materials and Methods We performed a retrospective audit of changes in RBC transfusion burden in 51 patients with predominantly higher risk MDS (26·5% high risk, 51·0% intermediate‐2) who received AZA. Transfusion requirements were audited 6 months prior to and up to 18 months after therapy initiation, and data were analysed using a generalized linear mixed model. Results At baseline, 30 patients (58·8%) were transfusion dependent (TD). Seventeen patients (56·7%) achieved transfusion independence (TI) by 18 months, and 8 of these patients (47·1%) achieved this response by 4 months on therapy. Achievement of TI was not consistently durable in these 17 patients, as 11 patients reverted to TD while on therapy. Meanwhile, 6 of 21 patients who were TI at baseline became TD on therapy. The monthly average of RBC units transfused decreased significantly beginning at 4 months, with a reduction from 2·50 units per month at baseline to 1·00 units per month at month 4. This 60% reduction was significant (P = 0·002) and sustained beyond 12 months. Conclusion These results bolster the notion that AZA significantly reduces transfusion burden and resource utilization and illustrate the limitations of the current WHO erythroid response criteria which do not account for differing durability and fluctuations of response.